# X-2y 2541

x-2y + 2z = -1
2x + y-z = 3
3x + 2y + z = 2

x =  1
y =  0
z =  -1

### Step-by-step explanation:

x-2y+2z=-1
2x+y-z=3
3x+2y+z=2

x-2·y+2·z=-1
2·x+y-z=3
3·x+2·y+z=2

x-2y+2z = -1
2x+y-z = 3
3x+2y+z = 2

Pivot: Row 1 ↔ Row 3
3x+2y+z = 2
2x+y-z = 3
x-2y+2z = -1

Row 2 - 2/3 · Row 1 → Row 2
3x+2y+z = 2
-0.333y-1.667z = 1.667
x-2y+2z = -1

Row 3 - 1/3 · Row 1 → Row 3
3x+2y+z = 2
-0.333y-1.667z = 1.667
-2.667y+1.667z = -1.667

Pivot: Row 2 ↔ Row 3
3x+2y+z = 2
-2.667y+1.667z = -1.667
-0.333y-1.667z = 1.667

Row 3 - -0.33333333/-2.66666667 · Row 2 → Row 3
3x+2y+z = 2
-2.667y+1.667z = -1.667
-1.875z = 1.875

z = 1.875/-1.875 = -1
y = -1.66666667-1.6666666666667z/-2.66666667 = -1.66666667-1.66666667 · (-1)/-2.66666667 = -0
x = 2-2y-z/3 = 2-2 · -0+1/3 = 1

x = 1
y = -0
z = -1

Our linear equations calculator calculates it. Did you find an error or inaccuracy? Feel free to write us. Thank you!

Tips for related online calculators
Do you have a system of equations and looking for calculator system of linear equations?